Pembelajaran Proyek Berbasis Ecoprint dalam menstimulasi kreativitas anak Sekolah Dasar Undar Andir - Ratu Yustika Rini; Imarananda Putri Imran; Erwin Hermawan; Islahiyah Islahiyah; Satriyah Triyastati; Haorah Haorah; Mahfudoh Tunisa; Maya Azzahra; Mova R Sianturi; Rena Rena; Diah Adawiyah; Anisa Arlinda Putri; Shinta Damayanti; Yeni Lasmawati (Pusat Riset dan Inovasi Nasional, 2024)
Utilization of natural resources available in the school environment is very weak. Meanwhile, the key to implementing interesting learning is a teacher and students who are able to have good creativity. These emerging problems prompted the KKM Universitas Bina Bangsa team to carry out Community Service by carrying out ecoprint-based project learning activities. The community service method is used by paying attention to the first flow, namely providing understanding, preparing a plan for ecobricks project learning activities and small-scale ecobricks trials first with the teacher. The next stage is the implementation of ecobrick project activities by starting with an apperception about ecobricks, then a demonstration of the ecobrick project, and finally the teacher invites students to be able to explore with the media available in the school environment and the tools provided by the teacher. The results found were that all students were able to show their creativity in ecoprint activities.